Examining Demographic and Clinical Traits in Neurofibromatosis Type 1 Patients: Insights into Vitamin D Levels and Connections with Nevus Anemicus and Neurofibromas - Vahid Ahmadi; Nazli Karimi; Arsoy S. Evans; Ayşen Karaduman (Indian Journal of Dermatology)
Aim: This article aims to examine the demographic and clinical traits of neurofibromatosis type 1 (NF1) patients, particularly focusing on the potential links between vitamin D levels, BMI, and dermatological features. Methods: A retrospective review of medical records involving 128 patients diagnosed with neurofibromatosis type 1 (NF1) over a 3-year-period was conducted. The analysis emphasized investigating the demographic and clinical characteristics of the patients while evaluating key parameters. Result: Nevus anemicus was present in 32.8% of NF1 patients, and a significant association was found between nevus anemicus and low vitamin D levels (P = 0.001). We also observed a notable correlation between low vitamin D levels and an increased likelihood of neurofibromas (P < 0.001). Additionally, there appears to be an inverse relationship between serum vitamin D levels and the number of neurofibromas. Conclusion: Our study suggests a correlation between lower vitamin D levels and key dermatological characteristics in neurofibromatosis type 1 (NF1) individuals. Specifically, we observed associations with nevus anemicus prevalence and increased neurofibromas. This observation enriches NF1’s understanding, offering practical implications for patient management by emphasizing the importance of monitoring and addressing vitamin D levels.